Faktor-Faktor Yang Berhubungan Dengan Kepatuhan Perawat Dalam Melakukan Hand Hygiene Di Ruangan Rawat Inap, Rawat Jalan Dan UGD Rumah Sakit Mitra Husada Tangerang - Vebry Haryati Lubis; Sugiyono Sugiyono; Rosmala Dewi (STIKes IMC Bintaro, 2023)
ABSTRACT Introduction: Compliance is the overall (total) understanding and activity between internal factors and external factors. Internal factors include knowledge, intelligence, perception, emotion, motivation and so on which function to process external stimuli. External factors include the surrounding environment, both physical and non-physical, such as climate, humans, socio-economics, culture and so on (Notoatmodjo, 2018). Compliance in hand hygiene is very important for nurses. This is because the lack of nurse compliance can have several impacts. Mitra Husada Hospital sets a target of 100% achieving hand hygiene compliance (Mitra Husada Hospital, 2022). Research Objectives: To find out the factors related to nurse compliance in carrying out hand hygiene in the Inpatient, Outpatient and Emergency Room at Mitra Husada Hospital Tangerang in 2022. The form of the research used was descriptive analytic with a cross sectional approach. Sampling technique with non random sampling probability. So that the sampling in this study is total sampling. The instruments used are questionnaires and observation sheets, while the statistical test uses the Chi Square test. The results of the study: showed that there was a relationship between factors including the level of knowledge, attitudes, motivation, hand hygiene facilities and supervision with nurses' compliance in carrying out hand hygiene in the Inpatient, Outpatient and Emergency Room at Mitra Husada Hospital Tangerang in 2022 with test results statistic that is P Value 0.000. Suggestion: information and experience obtained from researchers or research processes that have been carried out can be input for institutions to always pay attention and motivate employees, especially nurses in doing hand hygiene before and after doing activities at Mitra Husada Hospital Tangerang.